EROTYPE IDENTIFICATION OF VIBRIO CHOLERAE BACTERIAWHICH ISOLATED FROM ICE AMONGTUBE AND CUBE ICE TYPE IN FOOD AND BEVERAGES SELLER AT DENPASAR CITY, BALI - Dhinarananta, IGP; Wijaya P, IGM; WS, P Ananta; A, P Yuniadi; Hendrayana, M Agus (E-Jurnal Medika Udayana; vol 3 no 1 (2014):e-jurnal medika udayana, 2014)
Cholera is a type of watery diarrhea with specific sign stool containing mucus which resembles rice water. Cholera caused by gram negative bacteria Vibrio cholerae (V. Cholerae). The transmissions of bacteria were through a contaminated food or water. Bali is an international tourism destination with tropical weather where ice is widely used in food and beverage which bring a risk of cholera through a contaminated ice.Ices have a risk of bacterial contamination whether from the making and the usage process. Type of ice that widely used were cube and tube ice which each of them have a different in making and usage process. The purpose of this study is to obtain the contamination of V.cholera in cube and tube ice. The method of this study is descriptive observational study with quota sampling technique. Sample were obtained from a restaurants and street vendor which use a block and tube ice with total 10 sample and 5 for each type of ice.Sample then cultured in Alkaline Peptone Water(APW) and Thiosulfate Citrate Bile salt Sucrose(TCBS) agar. Bacteriacolony then identified using a gram staining and Latex Serotyping. The result are 3 over 5 (60%) sample of cube ice contaminated by V.cholera O1 Inaba serotype and 3 over 5 (60%) sample of tube ice contaminated by V.cholera O1 Inaba serotype.
Keywords: V. cholerae, Bali, Block Ice, Tube Ice, APW, TCBS, Latex Serotyping